Analisis Tingkat Literasi Sains Siswa Sekolah Dasar dalam Pembelajaran IPA - Nugraha, Dhike Softa Permata; Aynin Mashfufah; Siti Faizah; Siti Mas'ula; Riska Pristiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the level of scientific literacy of fourth-grade elementary school students in science learning. This study used a descriptive quantitative approach with 17 fourth-grade students as subjects at an elementary school in Nganjuk Regency. Data were collected through a scientific literacy test based on contextual science questions with indicators of understanding scientific concepts, explaining scientific phenomena, interpreting scientific information or data, and applying scientific knowledge in everyday life. Data were analyzed using descriptive statistics in the form of percentages and categories. The results showed that students' scientific literacy level was in the moderate category with an average of 59.75%. The highest indicator was the ability to understand scientific concepts at 68%, while the lowest indicator was the ability to interpret scientific information or data at 53%. These results indicate that students' scientific literacy needs to be improved through concrete, contextual, and interesting science learning.